The effect of fermentation process on increasing biodegradable organic waste reduction with Black Soldier Fly (BSF) larva bioconversion method - Aulia Rodlia Fitriana; Achmad Fajrul Akbar; Arseto Yekti Bagastyo (Center for Science and Technology, IAIN Surakarta, 2023)
. In 2021, Indonesia produced 64 million tons of waste, with market waste dominating at 22.7%. Organic waste processing can yield biogas, compost and can undergo the bioconversion process using Black Soldier Fly (BSF) larvae. BSF larvae lack cellulose-degrading enzymes. The addition of a fermentation process can increase growth and reduce waste. The research involved adding a fermentation process with two types of fermenters. Fermentation was carried out at different durations to determine to optimal fermentation period. The biodegradable waste utilised was vegetable and fruit waste from the market. As a control, organic waste without fermentation will also be utilized. The results indicated that fermentation had no significant effect on waste reduction. The reduction in fermented and non-fermented waste was 62.97% and 50.67%. Waste reduction is directly related to the larvae’s ability to consume waste. Fermented waste treated with Trichoderma (10 days) had exhibited peak larval growth at 18 days of age, whereas non-fermented waste reached its peak growth at 25 days. The residue from fermented waste had a lower quantity but a higher the C/N ratio of 89.37, while non-fermented waste residue had a greater quantity with a C/N ratio of 62.11.